Garbage Profiling – A Proposed System to rank localities based on waste segregation - Ahmed, Mohammed; Usmani, Nurulhaque; Khan, Javed; Khan, Shahnawaz; Shaikh, Imran (International Journal of Computer Sciences and Engineering, 2019)
To increase garbage processing and recycling, the Government implemented a Solid Waste Management Rule but it is not followed by some societies properly. And despite plastic ban plastic is used by some societies. To overcome above issues an app will be developed which take the image of garbage at garbage point and send it to the server for computation. In python, we incorporate the Machine Learning Module. Then by using convolutional a neural network technique, it will identify the garbage whether it is properly segregated or not and also how much amount of plastic is there in the garbage. Based on results we various communities will be rated. and notification will be sent to those communities who do not segregate their waste properly.